Conflicts in Physical Education Classes - A Systems Theoretical Analysis of the Teacher’s Perspective - Michelini, Enrico (Central European Journal of Educational Research, 2022)
This article presents the results of a systems theoretical analysis of conflicts in physical education classes from the teacher’s perspective. Building on the state of current research, a theoretical model to analyse the development and management of sport related conflicts in the school setting is elaborated. This model is used to examine written assignments collected at university seminars on conflicts in a German sport institute. At these seminars, sport science students submitted 40 detailed descriptions of conflicts in physical education classes, which were either collected through an interview or experienced directly in their role as teachers. The empirical material is analysed using qualitative content analysis. Based on a fictive case that is developed for exemplification purposes, all collected cases are considered against the background of the developed model. It differentiates between trivial, stable, slightly, and highly escalated conflicts and examines suitable management strategies. The study concludes that trivial conflicts are common in physical education classes, that teachers use different strategies to manage them, and that this issue is dealt with differently at the organisational level. This preliminary model can be improved through further empirical research that compares different school forms and levels of education at the national and international level.